Furrow Irrigated Raised Bed System in wheat and sugarcane to enhance system productivity - Singh, Ishwar (Indian Farming, 2017)
Wheat + sugarcane under Furrow Irrigated Raised Bed System improves sugarcane productivity registering 35% higher cane yield. It is the most remunerative and economical method of sugarcane planting with wheat.